ANATOMICAL CHARACTERISTICS AND CALCIFICATION PATTERNS OF COSTAL CARTILAGE IN VIETNAMESE ADULT CADAVERS (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the morphological characteristics and anatomical relationship between costal cartilage and the internal thoracic artery; To evaluate the prevalence and patterns of costal cartilage calcification in adult Vietnamese cadavers.Materials and methods: A descriptive cross-sectional study was conducted on 10 fresh, cold-preserved Vietnamese cadavers at the Department of Anatomy, University of Medicine and Pharmacy at Ho Chi Minh city.Results: VII costal cartilage provided the greatest length (mean 113.1-116.2 mm). The maximum thickness was observed at the VI costal cartilage (10.7 mm) and gradually decreased toward the VIII costal cartilage. The internal thoracic artery courses deep to the I through VI cartilages and begins to branch or deviate medially at the level of the VI costal cartilage in 95% of cases. The prevalence of costal cartilage calcification was 83 with the peripheral pattern being most common (30-80%). The severity was predominantly mild (grades 0 and 1 accounted for 90%).Conclusion: The VII costal cartilage serves as the optimal and safest graft source for reconstructive surgery due to its superior length and its location below the branching point of the internal thoracic artery. Furthermore, the predominance of peripheral calcification allows surgeons to effectively harvest the central cartilaginous core.
Keywords: Costal cartilage, internal thoracic artery, costal cartilage calcification, structural rhinoplasty.